Kerinci District Football Coaching Program Evaluation Innovation: CIPP Model Approach - Ozha Wahyu Pra Adha; Argantos; Emral; Ridho Bahtra; Fiky Zarya; Ali Munir (Jurnal Pendidikan Indonesia, 2023)
Achievement coaching is a program that has high value for an athlete, with the existence of achievement coaching can improve the quality possessed by an athlete. The low football achievements of Askab PSSI Kerinci can be seen from the medal tally of the last two periods of Porprov and the Jambi Governor's Cup. The purpose of this study is to evaluate the football achievement coaching program at Askab PSSI Kerinci. This type of research is qualitative using the CIPP model. The samples from this study were the chairman of KONI Kerinci Regency, PSSI Askab Board, coaches and athletes. Data collection through observation, interview and documentation using Data analysis in this study is uses divided into three stages, namely data reduction, data presentation and conclusion drawing. The evaluation results show that (1) The context aspect of the Askab PSSI Kerinci coaching program has a written management structure that has been approved by the Jambi PSSI Asprov (2) The input aspect, the trainer has an AFC C license and has a training program, but the completeness of facilities and infrastructure is inadequate and still below the established standards (3) Process aspect, the implementation of the training program is in accordance with the design made by the trainer but the short implementation time of 2-3 weeks makes the training program not running effectively (4) Product aspect, getting 2nd place at the 2019 Pre-Porprov event and the 2020 Governor's Cup.